Financing of a limited liability company by capital contributions - basic legal characteristics, company law and tax law advantages and disadvantages - - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Financing of a limited liability company by its members takes place at the time of establishment or during its existence on different legal bases. Given that different ways of financing the company by the members were the subject of individual analysis in different research works, the subject of consideration in this paper will be the economic purpose and the company-legal and tax-legal advantages and disadvantages of financing the company through payments or contributions in kind. The advantages and disadvantages of this type of company financing are viewed both from the perspective of the interests of the members of the company (investors) and from the perspective of the interests of the company in which the investment is made. Finally, a special place in the work is occupied by considerations about the so-called hidden contributions in kind, with the basic conclusion that the Serbian Company Law does not contain rules that would "suppress" the problem of the so-called hidden contributions in kind, nor a sufficiently detailed regulation that would prevent circumvention of the rule on the prohibition of returning contributions to company members. Such a lack of regulation can go not only to the detriment of the company’s interests, but also to the detriment of the interests of the company’s creditors.